2018
DOI: 10.3390/agronomy8080129
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation and Counting of Aphid Nymphs on Leaves Using Convolutional Neural Networks

Abstract: The presence of pests is one of the main problems in crop production, and obtaining reliable statistics of pest infestation is essential for pest management. Detection of pests should be automated because human monitoring of pests is time-consuming and error-prone. Aphids are among the most destructive pests in greenhouses and they reproduce quickly. Automatic detection of aphid nymphs on leaves (especially on the lower surface) using image analysis is a challenging problem due to color similarity and complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 24 publications
0
18
0
3
Order By: Relevance
“…In experiments, 102 aphid nymph images in practical experimental environments were collected and analyzed to detect the number of aphid nymphs on each image for the evaluation of the proposed method. The results showed that the mean count error and F1-score of the proposed method were 1.2 and 0.9606, respectively [41].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In experiments, 102 aphid nymph images in practical experimental environments were collected and analyzed to detect the number of aphid nymphs on each image for the evaluation of the proposed method. The results showed that the mean count error and F1-score of the proposed method were 1.2 and 0.9606, respectively [41].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 98%
“…Three papers on DL-based image recognition techniques for agronomy applications are as follows: (1) "Automatic segmentation and counting of aphid nymphs on leaves using convolutional neural networks," by Chen et al [41]; (2) "Estimating body condition score in dairy cows from depth images using convolutional neural networks, transfer learning, and model ensembling techniques," by Alvarez et al [42]; and (3) "Development of a mushroom growth measurement system applying deep learning for image recognition," by Lu et al [43].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 99%
“…Although the concept of neighborhood density is introduced to initialize the clustering center in the literature and it does show higher segmentation accuracy than the above two, however, FCM is effective only for the recognition of mature tomatoes in close shots similar to [14]. As shown in image 4,7,8,10,17,19, and 20, all tomatoes have very high visual saliency in the images. In our database, the existence of green tomatoes and leaves under a busy background in different growth cycles is common, which brings great interference to the initial clustering center in the color space.…”
Section: Analysis Of Comparative Experimentsmentioning
confidence: 99%
“…The vision information of greenhouse crops is of great significance for plant phenotype analysis, which has been applied to provide guidance to improve crop cultivation in many studies [1][2][3][4][5]. It is obvious that an automatic, accurate, and high-throughput imaging processing technique-with high sensitivity for plant phenotypic research-not only lays a visual foundation for analyzing the effect on the environment in production, but is also conducive to comprehensive research of internal and external factors on the physical and biochemical characteristics of plants.…”
Section: Introductionmentioning
confidence: 99%
“…(d) Segmentação utilizando o método 2. (e) Segmentação usando o método proposto Fonte: Adaptado de(CHEN et al, 2018)…”
unclassified